2019
DOI: 10.3390/polym11020198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Panel Construction on the Ballistic Performance of Multiply 3D through-the-Thickness Angle-Interlock fabrIc Reinforced Composites

Abstract: This paper studied the ballistic performance of 3D woven angle-interlock fabric reinforced composites with different types of panel construction. Two types of composites P10B and P17C were designed to have the same areal density of around 12 kg/m2 although they both had different ply areal densities and consisted of different numbers of plies. Non-perforated ballistic impacts were conducted on the two types of panels under the same level of impact energy. Post-mortem examination on the non-perforated panels wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…According to Min et al [35], the region where delamination is most widespread is the area where the impactor stopped, which is the last penetrated layer. Thus, the delamination is most notable with the conical projectile where the penetration into the specimen is higher than the blunt, Figure 10a.…”
Section: Failure Mechanism By Ct Imagesmentioning
confidence: 99%
“…According to Min et al [35], the region where delamination is most widespread is the area where the impactor stopped, which is the last penetrated layer. Thus, the delamination is most notable with the conical projectile where the penetration into the specimen is higher than the blunt, Figure 10a.…”
Section: Failure Mechanism By Ct Imagesmentioning
confidence: 99%
“…The Z-warp (interlocking warp) yarns in 3D fabrics bind the weft layers together, providing enhancement through the panel thickness, and effectively suppressing large local deformations upon impact [8]. Moreover, previous studies shown that the 3D woven through-the-thickness angle-interlock fabrics exhibit excellent mouldability, which can reinforce complex doubly-curved shapes, such as female body armor and ballistic helmets, in single-piece [9][10][11]. However, the differences in the ballistic responses and failure mechanisms of the 2D plain and 3D angle-interlock fabrics are still not understood.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, composite material, which is reinforced with 3D warp interlock fabric, exhibit higher inter-laminar fracture toughness owing to the presence of binding warp yarns within all the structure [2]. Additionally, 3D woven composites have higher delamination resistance, which is a suitable property for thick composite material [36] as well as for ballistic applications [710].…”
Section: Introductionmentioning
confidence: 99%